2020
DOI: 10.1590/fst.32818
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest 1-methylcyclopropene treatments maintain the quality of Rosa sterilis D. shi during storage

Abstract: 1-Methylcyclopropene (1-MCP) is an inhibitor of ethylene action by binding at the receptor site, and has been widely used in postharvest technology to prolong the storage life of many fruits and vegetables. Postharvest 1-MCP treatment, which could retard lignin and cellulose accumulation, and delay senescence, have been largely reported in bamboo shoot (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…[23,[27][28][29] Postharvest 1-MCP treatment, which could effectively suppress respiration rates, reduce chilling injury, retard lignin and cellulose accumulation, and delay senescence, have been largely reported in bamboo shoot, [8,14] Tsai Tai, [11] loquat fruit, [10] kiwifruit, [12] and Rosa sterilis D. shi. [13] Our research revealed that postharvest 0.5 μL L −1 1-MCP treatment suppressed the respiration rate, delayed the increased length of pod tendon and electrolyte leakage, and retarded the decrease in length of pod tendon, relative thickness of pods and firmness, it also maintained the quality of fresh common bean, this is consistent with our previous results. [15,19,20] The remarkable effect of 1-MCP treatment on suppressing respiration rate during storage has been reported in green bean [6] and snap bean.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[23,[27][28][29] Postharvest 1-MCP treatment, which could effectively suppress respiration rates, reduce chilling injury, retard lignin and cellulose accumulation, and delay senescence, have been largely reported in bamboo shoot, [8,14] Tsai Tai, [11] loquat fruit, [10] kiwifruit, [12] and Rosa sterilis D. shi. [13] Our research revealed that postharvest 0.5 μL L −1 1-MCP treatment suppressed the respiration rate, delayed the increased length of pod tendon and electrolyte leakage, and retarded the decrease in length of pod tendon, relative thickness of pods and firmness, it also maintained the quality of fresh common bean, this is consistent with our previous results. [15,19,20] The remarkable effect of 1-MCP treatment on suppressing respiration rate during storage has been reported in green bean [6] and snap bean.…”
Section: Discussionsupporting
confidence: 91%
“…Postharvest 1-MCP treatment, which could retard lignin and cellulose accumulation, and delay senescence, have been largely reported in bamboo shoot, [8,9] loquat fruit, [10] Tsai Tai, [11] kiwifruit, [12] and Rosa sterilis D. shi. [13] In postharvest application of 1-MCP, increasing evidence has indicated that 1-MCP treatment can inhibit the expression of ethylene receptor (ETR), EIN3-like, expansin, and CAD gene, reduce the activity of 1-aminocyclopropane-1-carboxylic acid oxidase (ACO), polyphenoloxidase (PPO), PAL, CAD, POD, and laccase (LAC) enzyme, suppress the increase of cellulose content, and thus inhibit the lignocellulose of fruits and vegetables. [8,[12][13][14][15] It has been shown that 1-methylcyclopropene (1-MCP) delays the senescence of fresh green beans during storage [6] and reduces the chilling injury symptoms of snap beans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study it was proved that CaCl2 enhance grapefruit texture (16). There were investigation on 1methylcyclopropene on Rosa sterilis D. shi fruits (17). They showed that postharvest treatment with 1.0 μL/ L 1-MCP suppressed the respiration rate, ethylene production rate and peroxidase activity in Rosa sterilis D. shi fruits, inhibited the transport of Note: the values were expressed as the mean of twenty two samples; the same characters (denoted above), the difference between them was not significant (α = 5%).…”
Section: Effect Of Cacl2 Concentration and Immersion Time On Firmness And Weight Loss Of Watermelon After 3 Days At Ambient Storagementioning
confidence: 98%
“…The respiration rate and ethylene production of kiwifruit were determined according to Xie et al (2020), and expressed as mg kg −1 h −1 CO 2 and mg kg −1 h −1 C 2 H 4 , respectively. [30] The core, seeded pulp, and seedless pulp of 40 fruits were collected, and the remaining 20 fruits were taken as the whole fruit with a thickness of 2 cm in the middle of the core, seeded pulp, and seedless pulp (as shown in Figure 1).…”
Section: Evaluation Of Respiration Rate and Ethylene Productionmentioning
confidence: 99%